Isolation and genetic characterization of mother-of-snow-white, a maternal effect allele affecting laterality and lateralized behaviors in zebrafish - Domenichini, Alice; Dadda, M.; Facchin, L.; Bisazza, A.; Argenton, F. (Public Library of Science, 2011)
In the present work we report evidence compatible with a maternal effect allele affecting left-right development and functional lateralization in vertebrates. Our study demonstrates that the increased frequency of reversed brain asymmetries in a zebrafish line isolated through a behavioral assay is due to selection of mother-of-snow-white (msw), a maternal effect allele involved in early stages of left-right development in zebrafish. msw homozygous females could be identified by screening of their progeny for the position of the parapineal organ because in about 50% of their offspring we found an altered, either bilateral or right-sided, expression of lefty1 and spaw. Deeper investigations at earlier stages of development revealed that msw is involved in the specification and differentiation of precursors of the Kupffer's vesicle, a structure homologous to the mammalian node. To test the hypothesis that msw, by controlling Kupffer's vesicle morphogenesis, controls lateralized behaviors related to diencephalic asymmetries, we analyzed left- and right-parapineal offspring in a "viewing test". As a result, left- and right-parapineal individuals showed opposite and complementary eye preference when scrutinizing a model predator, and a different degree of lateralization when scrutinizing a virtual companion. As maternal effect genes are expected to evolve more rapidly when compared to zygotic ones, our results highlight the driving force of maternal effect alleles in the evolution of vertebrates behaviors. © 2011 Domenichini et al.